2016
DOI: 10.17795/jjcdc-29565
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Idea about Cigarettes and Smoking

Abstract: Background: Tobacco smoking is attributed to pediatric disease and pediatric epidemics. This study aimed to indicate the attitudes of four-to six-year-old children toward cigarettes. Methods: This cross sectional study was conducted by a questionnaire in 2011. Hundred and forty-five, children, aged four to six years, were randomly selected from eight kindergartens located in all four areas of Ahvaz. Descriptive statistics was used to analyze demographic data, Chi-square test to compare qualitative variables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…To prevent expansion of addiction at different levels, implementation of such programs in Iran is recommended (48)(49)(50). Since the authors found no similar studies on the effectiveness of life skills education program in social relationships of drug addicts in Iran and this method is barely known in Iran, the present study tried to introduce the program as an affordable and feasible approach.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent expansion of addiction at different levels, implementation of such programs in Iran is recommended (48)(49)(50). Since the authors found no similar studies on the effectiveness of life skills education program in social relationships of drug addicts in Iran and this method is barely known in Iran, the present study tried to introduce the program as an affordable and feasible approach.…”
Section: Discussionmentioning
confidence: 99%